2005
DOI: 10.1167/iovs.05-0043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of P2Y Receptor Subtypes in Human Müller Glial Cells by Physiology, Single Cell RT-PCR, and Immunohistochemistry

Abstract: The presented data obtained by different techniques revealed that human Müller cells express P2Y1, P2Y2, P2Y4, and P2Y6 receptors. The specific roles of these receptor subtypes in retinal physiology and/or pathophysiology remain to be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 53 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…Indeed, in our hands, ATP was found to stimulate calcium influx in GS and GFAP-positive cells, possibly through ionotropic P 2 X 7 receptors, since these effects were blocked by brilliant blue G (not shown). Several purinergic ionotropic (Pannicke et al 2000) and metabotropic (Fries et al 2005) receptors have been identified in Müller glia and in retinal progenitors possibly mediating proliferation induced by ATP (Sholl-Franco et al 2010). Also, ATP is known to activate microglia in other areas of the CNS ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our hands, ATP was found to stimulate calcium influx in GS and GFAP-positive cells, possibly through ionotropic P 2 X 7 receptors, since these effects were blocked by brilliant blue G (not shown). Several purinergic ionotropic (Pannicke et al 2000) and metabotropic (Fries et al 2005) receptors have been identified in Müller glia and in retinal progenitors possibly mediating proliferation induced by ATP (Sholl-Franco et al 2010). Also, ATP is known to activate microglia in other areas of the CNS ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the expression and function of P2Y receptors remain difficult due to limitations of available pharmacological tools and antibodies. Pharmacological experiments on M€ uller cell swelling (Uckermann et al, 2005;Wurm et al, 2008) and calcium imaging data (Li et al, 2001) indicate an expression of P2Y 1 in rat M€ uller cells; otherwise, several P2Y receptor subtypes have been found on tiger salamander (Reifel-Saltzberg et al, 2003) and human M€ uller cells (Fries et al, 2005), respectively. However, since most P2 receptor agonists and antagonists are rather unspecific, the interpretation of these data should be done with caution.…”
Section: Introductionmentioning
confidence: 99%
“…P2Y1 receptor has been reported to be expressed in the retina of rat [8,11,12], developing chick embryo [13], and human glial cells [10]. However, little information is available to understand the role of P2Y1 activation not only for physiologic action but also for tumorigenesis in retinoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Expression profiles and physiological characteristics of P2Y receptors have been investigated in various retinal tissues. Several subtypes of P2Y receptors, including P2Y1, P2Y2, P2Y4, and P2Y6, are expressed in retinal neurons and glial cells [8,[10][11][12][13]. Particularly, P2Y2 receptor mRNA has been verified in the ganglion cell layer and the inner nuclear layer of adult Rhesis Macaques and albino rabbits [9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation